Standard molar enthalpy of formation of 2,4,6-trimethylpyridine - Silva, Manuel Ribeiro da (1997)
The standard (p°=0.1 MPa) molar enthalpy of formation for liquid 2,4,6-trimethylpyridine was derived from the standard molar enthalpy of combustion, measured by static bomb combustion calorimetry in oxygen, at the temperatureT=298.15 K: ΔfHm=−(31.0±2.3) kJ·mol−1.